Ailanthone Inhibits Cell Proliferation in Tongue Squamous Cell Carcinoma via PI3K/AKT Pathway. (1st November 2022) - Wang, Shuhan; Cui, Qixiao; Chen, Xiaoyu; Zhu, Xuejie; Lin, Kehao; Zheng, Qiusheng; Wang, Yuliang; Li, Defang
Abstract : Tongue squamous cell carcinoma (TSCC) is the most widespread and invasive subtype of oral cancer with high recurrence rates. Ailanthone (AIL) is an active ingredient in the plant extracts of Ailanthus altissima (Mill . ) Swingle . Here, we showed that AIL inhibited the proliferation of human TSCC, the cell viability of Cal-27 and Tca8113 was significantly decreased after AIL treatment for 24 h. Hoechst 33258 staining demonstrated apoptotic characteristics (such as chromatin aggregation) after AIL treatment. The ratio of early- and late-apoptotic cells in AIL-treated Cal-27 and TCA8113 cells increased remarkably when compared with the control group. Bcl-2/Bax ratio and the levels of PARP1, caspase-9, and caspase-3 decreased after AIL treatment, accompanied by significant increase of cleaved PARP1, cleaved caspase-9, and caspase-3 in Cal-27 and TCA8113 cells. Meanwhile, AIL led to Cal-27 cell cycle arrest at G2/M phase. Western blot implied decreased levels of CDK1 and cyclin B1 after AIL treatment. The level of phospho-PI3K p55 subunit and p-Akt were significantly downregulated by AIL in both Cal-27 and TCA8113 cells. These findings implied the potential applications of AIL in the treatment of human TSCC.